Big Data - a Challenge for Urban Transport Managers - Anna Urbanek (Communications - Scientific letters of the University of Zilina, 2017)
Big data is a term used to describe large, variable and very diverse data sets, which are very difficult to process and analyse, but on the other hand which are extremely valuable from the point of view of gaining knowledge, for example, on consumer behaviour or real-time changes in a specific market. Automated fare technologies in public urban transport are implemented ever more widely in many cities worldwide. Because of these technologies the public transport organisers have access to large data sets, which create new possibilities in the decision-making process. The aim of the paper is to discuss the role of big data in the decision-making process in urban public transport and also the main barriers to big data use in the urban mobility management.